2021
DOI: 10.1177/13623613211020916
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic coping and coparenting among couples after their child’s recent autism diagnosis

Abstract: This study explores how parenting couples use their relationship to support each other after their child’s autism diagnosis by assessing the role of dyadic coping and parenting sense of competence as predictors of their coparenting quality. Mothers and fathers raising a child on the spectrum ( N = 70 couples) individually completed self-report questionnaires measuring stress appraisal, dyadic coping, parenting sense of competence, and coparenting. Parents were recruited 1–36 months after their child’s autism d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…Prior research (Brisini and Solomon, 2020a, Solomon et al, 2016) has shown that children with ASD are more likely to feel safe when their parents have a strong and intimate relationship. Moreover, parental intimacy can positively impact children's social skill development (Downes et al, 2022). When parents share an intimate relationship, they model healthy social behaviors and communication styles for their children, who can learn from their example and subsequently apply these behaviors and communication styles to their own social interactions (Ledermann and Kenny, 2012).…”
Section: Impact Of Parental Intimacy On Dyadic Coping (Dc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research (Brisini and Solomon, 2020a, Solomon et al, 2016) has shown that children with ASD are more likely to feel safe when their parents have a strong and intimate relationship. Moreover, parental intimacy can positively impact children's social skill development (Downes et al, 2022). When parents share an intimate relationship, they model healthy social behaviors and communication styles for their children, who can learn from their example and subsequently apply these behaviors and communication styles to their own social interactions (Ledermann and Kenny, 2012).…”
Section: Impact Of Parental Intimacy On Dyadic Coping (Dc)mentioning
confidence: 99%
“…Dyadic coping (DC) (Downes et al, 2022) refers to parents' collaborative efforts to manage stress, and it is an important promoting factor for resilience in couples facing adversity. However, little is known about how parental intimacy and self-disclosure in uence dyadic coping among parents with a child with ASD who is starting school.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological and pedagogical support for the quality of life of persons with disabilities. International Journal of Health Sciences, 6(2), 1108Sciences, 6(2), -1122 https://doi.org/10.53730/ijhs.v6n2.11330 Downes et al (2022), in their study, investigated how parenting couples use their relationships to support each other after their child's autism diagnosis, assessing the role of dyadic coping and sense of parenting competence as predictors of quality co-parenting. Mothers and parents raising a child on the spectrum (N = 70 pairs) individually completed self-assessment questionnaires measuring stress ratings, dyadic coping, sense of parenting competence, and shared paternalism.…”
Section: Pedagogical Science Has Never Abandoned This Term the More S...mentioning
confidence: 99%
“…The growing number of autistic children poses an increased need for services to support these children and their families. Parents 1 of children with autism have described receiving their child’s autism diagnosis as intensely emotional and followed by mixed emotions including relief, despair, confusion, self-blame, and increased stress (Downes et al, 2022; Rabba et al, 2019). Parents report undergoing an adjustment period that was accompanied by feelings of isolation and loneliness, stressful transitions, and difficulties in managing their home and work responsibilities and making treatment decisions for their child’s needs (Keen et al, 2010; Mandell & Salzer, 2007; Rabba et al, 2019; Watt & Wagner, 2013).…”
mentioning
confidence: 99%